Acquired language disorders beyond aphasia: foreign accent syndrome as a neurological, speech, and psychiatric disorder - Longman, R. Stewart; Schwartz, Flint D. (Frontiers in Psychology, 2025)
This study examines historical conceptualizations of ‘foreign accent syndrome’ after brain trauma or as an aspect of psychiatric presentations, in addition to comparisons with current conceptualizations. Although classical understanding of aphasias as language disorders developed between 1861 and 1885, descriptions of non-aphasic speech disorders emerged later. Acquired accent following a stroke was first described in 1907 by Pierre Marie (1853–1940) in the context of the localizationist versus holistic debate. Early characterizations by Marie, Arnold Pick (1851–1924), and G.H. Monrad-Krohn (1884–1964) identified persisting speech changes following initial aphasia, which, from a contemporary viewpoint, provide insights into the dynamic nature of recovery after cerebral injury. These cases significantly contributed to the understanding of the neurological foundations of prosody and the non-linguistic aspects of speech. A deeper understanding of this disorder awaited contributions from various fields, including linguistics, speech-language pathology, psychiatry, and neuroimaging. Notably, there is an unusual gap in psychiatric causation reports prior to 1960, despite some intriguing indications from Josef Breuer’s account of Anna O (1895). This study explores how historical perspectives continue to influence current conceptualizations of foreign accent syndrome.